Socialization Android-Based Electronic Screening Test Epidemiology (E-Steco 19) In Indonesia and Timor Leste - Noor, Frieda Ani; Prastyoningsih, Aris; Kanita, Maria Wisnu P.; P, Oliva Virvizat; ., Ernawati; Safitri, Wahyuningsih; Rahayu, Retnaning Tyas (RA Journal of Applied Research, 2023)
Introduction: A statement of being in good health is one of the prerequisites as a lecturer or employee at Kusuma Husada University, in which an employee must be declared in good health to prove that an employee is healthy and ready to work, without any serious unhealthy obstacles. Health checks by computerized epidemiology screening test will speed up the process and assist the doctor The development of health applications using the epidemiological screening test method for lecturers and Studends, at the Kusuma Husada University Health Clinic Indonesia Health screening tests quick and efficient in accordance with existing data, and give the result of employee health data directly. The purpose of this study is to make it easier to detect the health status of Kusuma Husada University lecturers and Studends, which is used for one of the prerequisites for a work contract with a health application using an epidemiological screening test method. Methods: Data collection was done by qualitative method and carried out from February to August 2022. lecturers and Studends data retrieval is done using a digital questionnaire (online). Sample of this research is a studends, and employee at Kusuma Husada University Indonesia, the results is used to make applications (e-Steco). Results: E-Steco 19 is an Android-based application that is used to detect a person’s health using the screening test method. Data will be stored using Google Sheet and Google App Script. Thus, the data that has been collected from users who fill out a list of questions in the application can be downloaded and processed according to the needs. Data can be downloaded via the link. The e-Steco result can be processed in such a way that the data can be used as material for decision making. E-Steco 19 consists of 14 questions for health screening. Here we show the results of data processing from e-Steco 19 Result in the form of a pie chart. Results: The e-Steco 19 application has been completed and has also been running a test, so that it can make it easier to detect the health of lecturers and Studends, at Kusuma Husada University Indonesia. This application is still possible to be developed and used in Timor Leste University and Health Clinic.